M.T. Steyn se ervaring van die Anglo-Boereoorlog vanuit ‘n sielkundige perspektief (Historia, 2021)
At the outbreak of the Anglo-Boer War President M.T. Steyn was 42 years of age. This article examines Steyn's experience of the Anglo-Boer War from a psychological viewpoint, more specifically from a perspective dealing with the concept of stress and psycho-physiological disorders. A brief look is given to the work and theories of Hans Selye, the different types of stressors, the importance of general resistance resources and the constructs of salutogenesis and fortigenesis. Steyn's experiences are reviewed with emphasis on three matters: his ceaseless struggle to keep his ally, the Zuid-Afrikaansche Republiek (ZAR), from succumbing to peace overtures and his subsequent mistrust of his ally's leadership; his persistent problems among his own forces and lastly his frequent involvement in military operations. The conclusion is reached that Steyn's double vision and subsequent muscle disorder, seen in the light of today's scientific knowledge, and despite the various biomedical theories, can be described as a psycho-physiological disorder and not pathological in origin. It serves as an example of how stress can play a role in the course of history
Keywords: Anglo-Boer War; psycho-physiological disorders; salutogenesis and fortigenesis.; Zuid-Afrikaansche Republiek; military operations; muscle disorder; biomedical theories; stress